Management of State Owned Assets at Development Planning Agency: JEL Classification: H83, H72, H70, M48, D73 - Imran Imran; Gita Susanti (Journal La Bisecoman, 2025)
The management of Regional Government-Owned Assets (BMD) is an essential element in supporting the effectiveness of government administration and realizing accountable governance. This study aims to analyze the implementation of Regional Government Owned Asset management at the Regional Development Planning Agency (BAPPEDA) of Buton Regency based on Government Regulation Number 28 of 2020 and the Regulation of the Minister of Home Affairs Number 19 of 2016. This research employed a qualitative descriptive approach, with data collected through interviews, observations, and documentation. Data analysis was conducted using the interactive analysis model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results indicate that administratively, BMD management at BAPPEDA of Buton Regency has been implemented in accordance with applicable regulations, particularly in the aspects of planning, procurement, and asset administration. However, several obstacles remain in its implementation, especially in the aspects of asset use, utilization, security, maintenance, and supervision. Prominent issues include suboptimal needs analysis, weak recording of asset utilization, reactive maintenance practices, and the absence of clear Standard Operating Procedures and sanction mechanisms. This study concludes that although BMD management at BAPPEDA of Buton Regency has fulfilled administrative requirements, it has not fully reflected the principles of good governance, particularly accountability, effectiveness, and internal control. Therefore, strengthening internal regulations, improving employee discipline, and optimizing regional asset management systems are necessary.